2007
DOI: 10.1086/508733
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and Student Achievement in the Chicago Public High Schools

Abstract: We estimate the importance of teachers in Chicago public high schools using matched student-teacher administrative data. A one standard deviation, one semester improvement in math teacher quality raises student math scores by 0.13 grade equivalents or, over 1 year, roughly one-fifth of average yearly gains. Estimates are relatively stable over time, reasonably impervious to a variety of conditioning variables, and do not appear to be driven by classroom sorting or selective score reporting. Also, teacher quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
778
2
22

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 940 publications
(837 citation statements)
references
References 30 publications
35
778
2
22
Order By: Relevance
“…The partition in Eq. 1′ is by subject (math and reading) and grade (4)(5)(6)(7)(8), giving L = 2 × 5 = 10 cells, with weights W l i as in Eq. 5.…”
Section: Resultsmentioning
confidence: 99%
“…The partition in Eq. 1′ is by subject (math and reading) and grade (4)(5)(6)(7)(8), giving L = 2 × 5 = 10 cells, with weights W l i as in Eq. 5.…”
Section: Resultsmentioning
confidence: 99%
“…The results of these research efforts made clear that about 15% to 25% of the differences in students' achievement might be explained by the work of teachers (Aaronson, Barrow, & Sander, 2007;Bosker & Witziers, 1996;Brandsma & Knuver, 1989;Houtveen & Van de Grift, 2007a, 2007bHoutveen, Van de Grift, & Brokamp, 2014;Houtveen, Van de Grift, & Creemers, 2004;Rockoff, 2004;Roeleveld, 2003;Wijnstra, Ouwens, & Béguin, 2003). Students of teachers whose teaching quality is a full standard deviation higher, achieve 10% to 25% more learning gains (Aaronson et al, 2007;Bosker & Witziers, 1996;Brandsma & Knuver, 1989;Hanushek & Rivkin, 2010;Houtveen & Van de Grift, 2007a, 2007bKane & Staiger, 2008;Rivkin, Hanushek, & Kain, 2005;Rockoff, 2004;Roeleveld, 2003;Wijnstra et al, 2003).…”
Section: International Comparisons On the Quality Of Teachingmentioning
confidence: 99%
“…Students of teachers whose teaching quality is a full standard deviation higher, achieve 10% to 25% more learning gains (Aaronson et al, 2007;Bosker & Witziers, 1996;Brandsma & Knuver, 1989;Hanushek & Rivkin, 2010;Houtveen & Van de Grift, 2007a, 2007bKane & Staiger, 2008;Rivkin, Hanushek, & Kain, 2005;Rockoff, 2004;Roeleveld, 2003;Wijnstra et al, 2003). Thus, it is not only caused by the students' intelligence and socioeconomic background; the teacher matters in determining learning.…”
Section: International Comparisons On the Quality Of Teachingmentioning
confidence: 99%
“…For example, Jacob and Lefgren (2005) found that principal R CE M assessments of teachers explained only about 10 percent of the variation in classroom effects on reading and math. Similarly, Aaronson et al (2007) found that a host of teacher characteristics-including age, gender, race, educational background, tenure, and total experience-together only explained about 20 percent of the variation in classroom effects. Thus, it is likely that even a strong predictor of classroom effects could explain only a portion of this variation.…”
Section: Identifying Plausible R 2 Valuesmentioning
confidence: 93%